Belatacept‐based immunosuppression with simultaneous calcineurin inhibitor avoidance and early corticosteroid withdrawal: A prospective, randomized multicenter trial. Issue 4 (6th February 2020) - Woodle, E. Steve; Kaufman, Dixon B.; Shields, Adele R.; Leone, John; Matas, Arthur; Wiseman, Alexander; West‐Thielke, Patricia; Sa, Ting; King, Eileen C.; Alloway, Rita R.
Abstract : Simultaneous calcineurin inhibitor avoidance (CNIA) and early corticosteroid withdrawal (ESW) have not been achieved primarily due to excessive acute rejection. This trial compared 2 belatacept‐based CNIA/ESW regimens with a tacrolimus‐based ESW regimen. Kidney transplant recipients were randomized to receive alemtuzumab/belatacept, rabbit anti‐thymocyte globulin (rATG)/belatacept, or rATG/tacrolimus. The combinatorial primary endpoint consisted of patient death, renal allograft loss, or a Modification of Diet in Renal Disease–calculated eGFR of <45 mL/min/1.73 m 2 at 12 months. Results are reported by treatment group (alemtuzumab/belatacept, rATG/belatacept, and rATG/tacrolimus). Superiority was not observed at 1 year for the primary endpoint (9/107 [8.4%], 15/104 [14.4%], and 14/105 [13.3%], respectively; P = NS) for either belatacept‐based regimen. Differences were not observed for secondary endpoints (death, death‐censored graft loss, or estimated glomerular filtration rates < 45 mL/min/1.73 m 2 ). Differences were observed in biopsy‐proved acute cellular rejection (10.3%, 18.3%, and 1.9%, respectively) ( P < .001), but not in antibody‐mediated rejection, mixed acute rejection, or de novo donor‐specific anti‐HLA antibodies. Neurologic and electrolyte abnormality adverse events were less frequent under belatacept. Belatacept‐based CNIA/ESW regimens did not prove to be superior for the primary or secondary endpoints. Belatacept‐treated patients demonstrated an increase in biopsy‐proved acute cellular rejection and reduced neurologic and metabolic adverse events. These results demonstrate that simultaneous CNIA/ESW is feasible without excessive acute rejection. Abstract : This trial compares two belatacept‐based regimens that provide simultaneous calcineurin inhibitor avoidance (CNIA) with early corticosteroid withdrawal (ESW) with a tacrolimus‐based ESW regimen (with rATG induction) with belatacept‐based regimens demonstrating reduced neurologic and metabolic adverse events with modest increases in acute rejection compared to the tacrolimus‐based regimen.